A new species of Samba s. str. (Hymenoptera: Melittidae) from the Turkana Basin, Kenya with observations on the function of the metatibial spur in females - Packer, Laurence; Martins, Dino J. (Zootaxa, 2015)
The third known species of the Afrotropical subgenus Samba s. str. is described based upon eight females. This is the northernmost and also the most arid habitat record for the genus. Images are provided of the habitus and diagnostic features for the species as well as the subgenus and some notes on floral hosts and habitat are provided. The species is added to a morphology—based phylogeny for the genus and results of barcoding of some species of the genus are presented. Some unusual morphological features of the subgenus are discussed, in particular, the function of the remarkable metatibial spurs of the female is recorded as assisting with removal of pollen from a floral host.